Effectivity Study of “GAMA-AIMS” Application as Self-therapy in Overcoming Anxiety in Medical Students - Kusumadewi, Andrian Fajar; Naldi, Najla Humairah; Aulia, Afkar; Ismanto, Silas Henry (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
The anxiety level in medical students is higher compared to other majors, thereby necessitating effective intervention. Gadjah Mada Anxiety Intervention for Medical Students (GAMAAIMS) was developed to overcome anxiety using cognitive educational therapy. Therefore, this study aimed to determine the effectiveness of the GAMA-AIMS application by examining the differences in anxiety levels of health students before and after use. A quasi-experimental with pretests and post-tests was carried out on 86 students of Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada. Anxiety levels were measured using the Taylor Manifest Anxiety Scale (TMAS) questionnaire and statistical analysis was carried out through a paired T-test. Before the intervention, the prevalence of mild, moderate, and severe anxiety among participants was the same, at 33.3%. However, after the intervention, only 3.03% of participants experienced moderate anxiety, followed by severe and mild, with percentages of 12.12% and 84.84%, respectively. The results of the paired Ttest showed a fairly strong relationship between anxiety levels before and after the intervention (Cohen’s d coefficient = 1.04) which was statistically significant with a p-value of .000001 (p < .05). Therefore, the GAMA-AIMS mobile application was effective in reducing the anxiety levels of medical students.